Sustainable Coastal Community Empowerment through Ecology-Based Innovation in Batu Beriga Village, Central Bangka Regency - Marta, Dwi Jati; Yoga, Arry Aditsya (Journal of Rural and Regional Innovation Studies, 2025)
(1) Purpose: This study aims to analyze the forms, implications, opportunities, and challenges of ecology-based coastal community empowerment in Batu Beriga Village, Central Bangka Regency—an area where coastal residents often face marginalization and limited capacity in managing marine resources. Using Jim Ife’s empowerment framework, the research emphasizes the provision of resources, opportunities, and knowledge to strengthen community resilience. (2) Methods: A descriptive qualitative method was employed, with primary data collected through unstructured interviews involving 15 informants, including village officials, community members, tourism awareness groups, and staff from the Environment and Forestry Service and the Ministry of Environment and Forestry. (3) Results: The findings reveal that empowerment was implemented through the Mangrove Planting Cash-for-Work Program, which combined livelihood restoration with environmental rehabilitation. The program involved 40 local workers who received daily wages of IDR 100,000-120,000 to plant around 1,000 mangrove seedlings across 2.5 hectares of coastline, providing both short-term income and long-term ecological benefits. Economically, it improved household resilience during the post-pandemic recovery; socially, it fostered collaboration among local institutions and strengthened environmental awareness; ecologically, it contributed to shoreline protection and biodiversity enhancement. However, challenges persist, including low community participation, limited human resource capacity, and conflicts of interest related to coastal mining. (4) Conclusion: In conclusion, the study highlights the need for integrating ecological restoration with socio-economic empowerment through participatory governance, capacity building, and livelihood diversification to sustain coastal resilience.